Gluconeogenesis - Zhang, Weizhen (IntechOpen, 2017)
Gluconeogenesis, the metabolic process through which glucose or glycogen is synthesized from noncarbohydrate substrates, is critical for maintaining the plasma glucose level within a narrow range either in the fed or fasting (nutritional deprivation) state. Dysregulation of this pathway usually causes severe or even fatal outcomes. This book discusses a series of up-to-date topics about this critical process, including the fundamental biochemical reactions of glucose metabolism, the glucogenesis process in eukaryotic cells using the Dictyostelium discoideum as a model, the role of "gut-brain-liver axis" in the control of glucose homeostasis, and the new mathematic model for the monitoring and prediction of blood glucose. This book is written by international scientists with expertise in the study of gluconeogenesis. By presenting a clear and succinct review of the fundamentals of gluconeogenesis, it is expected to draw more attentions and stimulate more scientists to dedicate their researches in revealing the mechanism and its application of gluconeogenesis.